Do subfertile women adjust their habits when trying to conceive?. (2nd July 2016) - Joelsson, Lana Salih; Berglund, Anna; Wånggren, Kjell; Lood, Mikael; Rosenblad, Andreas; Tydén, Tanja
Abstract: Aim: The aim of this study was to investigate lifestyle habits and lifestyle adjustments among subfertile women trying to conceive. Materials and methods: Women ( n = 747) were recruited consecutively at their first visit to fertility clinics in mid-Sweden. Participants completed a questionnaire. Data were analyzed using logistic regression, t tests, and chi-square tests. Results: The response rate was 62% ( n  = 466). Mean duration of infertility was 1.9 years. During this time 13.2% used tobacco daily, 13.6% drank more than three cups of coffee per day, and 11.6% consumed more than two glasses of alcohol weekly. In this sample, 23.9% of the women were overweight (body mass index, BMI 25–29.9 kg/m 2 ), and 12.5% were obese (BMI ≥30 kg/m 2 ). Obese women exercised more and changed to healthy diets more frequently than normal-weight women (odds ratio 7.43; 95% confidence interval 3.7–14.9). Six out of ten women ( n = 266) took folic acid when they started trying to conceive, but 11% stopped taking folic acid after some time. Taking folic acid was associated with a higher level of education ( p  < 0.001). Conclusions: Among subfertile women, one-third were overweight or obese, and some had other lifestyle factors with known adverse effects on fertility such as use of tobacco. Overweight and obese women adjusted their habits but did not reduce their body mass index. Women of fertile age would benefit from preconception counseling, and the treatment of infertility should routinely offer interventions for lifestyle changes.